ANALISIS ANGGARAN PENDAPATAN DAN BELANJA DESA BERDASARKAN RASIO EFEKTIVITAS DAN RASIO PERTUMBUHAN PADA KANTOR DESA RANTAU PANJANG KECAMATAN LAWANG WETAN KABUPATEN MUSI BANYUASIN - Romanda, Candra; Septariani, Jumania (Jurnal Ilmiah Akuntansi Rahmaniyah, 2025)
This research aimed to measure the financial performance of Rantau Panjang Village in Lawang Wetan District, Musi Banyuasin Regency. It used effectiveness ratios and growth ratios for income and expenditure as its measurement methods. The study used both qualitative and quantitative approaches. It was carried out at the Rantau Panjang Village Office in Lawang Wetan District, using primary and secondary data sources collected through interviews and documentation. The data analysis technique involved calculating the effectiveness ratios and the growth ratios for income and expenditure. The findings indicated that the financial performance of the Rantau Panjang Village office from 2022 to 2024 showed a growth ratio for income averaging 36.45%, which was considered an increase. The expenditure growth ratio averages 33.96%, also indicating an increase. Meanwhile, the effectiveness ratio for income averages 100,00%, categorised as effective, while the effectiveness ratio for expenditure averages 96,88%, which was deemed effective.